Implementation Of The Final And Binding Principle In The Resolution Of International Business Disputes Through Arbitration - Wilson Wilson; Dwi Putra Jaya; Ferawati Royani (Utami Publisher, 2026)
International arbitration is one of the most widely used mechanisms for resolving cross-border business disputes due to its neutral, efficient, and legally certain nature. One of the fundamental characteristics of arbitration is the final and binding principle, which provides that arbitral awards are final and binding upon the parties and are not subject to ordinary legal remedies such as appeal or cassation as commonly found in court litigation. This principle constitutes a cornerstone of the effectiveness of international arbitration, as it ensures the prompt, definitive, and enforceable resolution of disputes across jurisdictions. Nevertheless, in practice, the implementation of the final and binding principle in Indonesia continues to face significant challenges, particularly at the stage of recognition and enforcement of international arbitral awards by national courts. The broad interpretation of the public policy exception and the tendency of judicial intervention often undermine the final and binding nature of arbitral awards, as reflected in several court decisions, including the case of Karaha Bodas Company L.L.C. v. Pertamina. This situation has resulted in tensions between the judicial authority of the state and Indonesia’s international obligations under the 1958 New York Convention. This research aims to analyze the legal regulation of the final and binding principle in the settlement of international business disputes through arbitration under Indonesian positive law, as well as to examine its practical implementation. The research adopts a normative legal research method employing statutory, conceptual, and case approaches. The legal materials used consist of primary, secondary, and tertiary sources, which are analyzed qualitatively. The findings of this study indicate that, normatively, the final and binding principle has been explicitly regulated under Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution and is consistent with the provisions of the 1958 New York Convention. However, in practice, its application has not been entirely consistent due to differences in legal interpretation and the prevailing judicial legal culture. Therefore, a more restrictive interpretation of the public policy exception, enhanced judicial understanding of international arbitration, and a stronger commitment to international legal standards are required to ensure legal certainty and to support a favorable investment climate in Indonesia.